Penggunaan Pendekatan Filsafat Clausewitz dalam Kajian Sejarah Peperangan Nabi Muhammad S.A.W. - Muhammad Affan (Madaniyah, 2018)
This following article will describe the concept of using Clausewitz’s philosophy approach in study the history of the battles of Prophet Muhammad (PBUH). The need for Clausewitz’s philosophy as an approach in study the battles history of Prophet Muhammad (PBUH) is an attempt to understand the battles of the Prophet Muhammad (PBUH) as a whole and more themed war. Expected by the use of Clausewitz’s philosophy approach, the mistakes in analyzing the history of the battle of Prophet Muhammad (PBUH) can be avoided.